Seasonal and Spatial Variations in Synechococcus Abundance and Diversity Throughout the Gullmar Fjord, Swedish Skagerrak - Laber, Christien P.; Pontiller, Benjamin; Bunse, Carina; Osbeck, Christofer M. G.; Pérez-Martínez, Clara; Di Leo, Danilo; Lundin, Daniel; Legrand, Catherine; Pinhassi, Jarone; Farnelid, Hanna (Frontiers in Microbiology, 2022)
The picophytoplankton Synechococcus is a globally abundant autotroph that contributes significantly to primary production in the oceans and coastal areas. These cyanobacteria constitute a diverse genus of organisms that have developed independent niche spaces throughout aquatic environments. Here, we use the 16S V3-V4 rRNA region and flow cytometry to explore the diversity of Synechococcus within the picophytoplankton community in a threshold fjord (20-34 PSU), the Gullmar Fjord on the west coast of Sweden. We conducted a station-based one-year time series as well as two transects of the fjord. These data revealed that within the large number of Synechococcus amplicon sequence variants (ASVs; 239 in total), prevalent ASVs phylogenetically clustered with clade representatives in both marine subcluster 5.1 and 5.2. The near-surface composition of ASVs shifted between the spring and summer season to a 5.1 dominant community, corresponding to the period of elevated Synechococcus abundances up to 9.3×104 cells ml-1. This seasonal dominance by 5.1 was observed over the length of the fjord (25 km), where shifts in community composition were associated with increasing depth. Unexpectedly, the community shift was not associated with changes in salinity. These results highlight how seasonal variations impact the dynamics of Synechococcus clades in a high latitude threshold fjord.